Effects of a Single Dose of Parecoxib on Inflammatory Response and Ischemic Tubular Injury Caused by Hemorrhagic Shock in Rats - Takaku, Mariana; Silva, Andre Carnevali da; Iritsu, Nathalie Izumi; Galvao Vianna, Pedro Thadeu [UNESP]; Machado Castiglia, Yara Marcondes [UNESP] (Hindawi Ltd, 2018)
Parecoxib, a selective COX-2 inhibitor, is used to improve analgesia in postoperative procedures. Here we evaluated whether pretreatment with a single dose of parecoxib affects the function, cell injury, and inflammatory response of the kidney of rats subjected to acute hemorrhage. Inflammatory response was determined according to serum and renal tissue cytokine levels (IL-1 alpha, IL-1 beta, IL-6, IL-10, and TNF-alpha). Forty-four adult Wistar rats anesthetized with sevoflurane were randomized into four groups: placebo/no hemorrhage (Plc/NH); parecoxib/no hemorrhage (Pcx/NH); placebo/hemorrhage (Plc/H); and parecoxib/hemorrhage (Pcx/H). Pcx groups received a single dose of intravenous parecoxib while Plc groups received a single dose of placebo (isotonic saline). Animals in hemorrhage groups underwent bleeding of 30% of blood volume. Renal function and renal histology were then evaluated. Plc/H showed the highest serum levels of cytokines, suggesting that pretreatment with parecoxib reduced the inflammatory response in rats subjected to hemorrhage. No difference in tissue cytokine levels between groups was observed. Plc/H showed higher percentage of tubular dilation and degeneration, indicating that parecoxib inhibited tubular injury resulting from renal hypoperfusion. Our findings indicate that pretreatment with a single dose of parecoxib reduced the inflammatory response and tubular renal injury without altering renal function in rats undergoing acute hemorrhage.